Manejo de enfermería en pacientes geriátricos con diagnóstico de accidente cerebro vascular en emergencia - Jumbo Vilela, Marco Jackson (2025)
The cerebral stroke is a dependent pathology with a major impact on public health, we approach the handling from the first moment, providing information about the steps that must be taken from the initial moment of the event, until the patient arrives at a health center. The objective was to identify nursing management in geriatric patients who present risk factors with cerebral strokes. The questionnaire was designed with 7 questions that involving nursing processes, communication, experience, patient safety and academic training in the management of critical patients in a certain time. Among the results deficiencies were found in the ACV handling by nursing in patients, who present this episode, lack of related knowledge with risk factors and assessment of neurological scales in these patients was analyzed. It's concluded that experience and training in the patient's care who suffer an ACV, can help to the correct making decisions being that immediate intervention is essential in these patients, whose purpose is to safeguard your life and avoid complications due to a delay in vital processes.